Map of North America. (1854)
Map shows upper Alaska as "Russian America" and lower Alaska as "Territory of the United States"; major cities, gold regions, areas of Native America habitation; "Polynia or Open Sea of the Russians," routes of Arctic exploration; shows railroads, counties, and cities in Canada on verso. Includes distances, dimensions of larger water bodies, and text notes. Relief shown by hachures and spot heights. Scale [ca. 1:35,000,000].